KRITIK HADIS BERBASIS USHUL FIQHIYAH: Reposisi Sunnah dalam Diskursus (Hukum) Islam Kontemporer - Fawaid, Achmad (STAIN Kediri, 2016)
This article is aimed to figure out the significant position of Hadis in the midst of contemporary discourse of Islamic legal theory in general, or in Ushul Fiqh in specific, on which Al Quran and Sunnah were based for law determination. In the history of Islamic development, there have been two major models of evaluation of Hadis, either by Muhaddits or by Ushuliyyun, which unfortunately offered no systematic methodology pertaining to make a clear of the position, of the function, and of the epistemological value of Hadis in legal theory (also in theological, philosophical, mystical fields of knowledge). This study attempts to (re)conceptualize a scope of Al Quran and Sunnah in the pre-classical Islamic period, which notably characterized an important hermeneutic relationship between both of them, and to make critical questions of classical Muhaddits’ and Ushuliyyun’s methodologies, which focused merely on ‘normative’ issues of isnad and mutawatir, contributing to the negation of primordial-hermeneutic relationship Al Quran and Sunnah and to the hypothetic assumption that the only objective of Hadis was to concern with textual authenticity (shahih) or narrators’ knowledge (mutawatir). By offering a new methodology which makes a question of both models of evaluation and provides a historical retention of hermeneutic relationship between Al Quran and Sunnah, this article was considerably to build an ethic-religious synthesis between Ulumul Hadis and Ushul Fiqh. Keywords: Al Quran, Sunnah, Hadis, Ushul Fiqh